Promoting Productive Uses of Electricity in Rural Electrification Programs : Experience from Peru - Franco, Janina; Bogach, V. Susan; Pérez Arroyo, Inés; Lasa, Maite (World Bank, Washington, DC, 2017)
Rural electrification programs can be more effective in stimulating economic growth, social development, and sustainable utility operations when they promote productive uses of electricity, as shown by a decade of experience in Peru. To obtain the desired benefits, rural electrification programs need to encourage and support installation and reliable operation of electrical equipment that makes production more efficient and profitable.